Zika virus infections imported from Brazil to Portugal, 2015. (2016) - Zé-Zé, L.; Prata, M.B.; Teixeira, T.; Marques, N.; Mondragão, A.; Fernandes, R.; Saraiva da Cunha, J.; Alves, M.J.
Abstract: Zika virus is an emerging arbovirus transmitted by Aedes sp. mosquitoes like the Dengue and Chikungunya viruses. Zika virus was until recently considered a mild pathogenic mosquito-borne flavivirus with very few reported benign human infections. In 2007, an epidemic in Micronesia initiated the turnover in the epidemiological history of Zika virus and more recently, the potential association with congenital microcephaly cases in Brazil 2015, still under investigation, led the World Health Organization (WHO) to declare a Public Health Emergency of International Concern on February 1, 2016. Here, we present the clinical and laboratory aspects related to the first four imported human cases of Zika virus in Portugal from Brazil, and alert, regarding the high level of traveling between Portugal and Brazil, and the ongoing expansion of this virus in the Americas, for the threat for Zika virus introduction in Europe and the possible introduction to Madeira Island where Aedes aegypti is present.